PENCIPTAAN SET FASHION TOURING DENGAN SENTUHAN ESTETIKA TRADISIONAL BALI - Noval Nur Akbar; I Made Jana; I Made Sumantra (Pusat Penerbitan LP2MPP ISI Denpasar, 2023)
The automotive industry remains an appealing market. The riding fashion trend is one of many new innovations that have emerged. This is the inspiration for creating touring fashion sets with traditional Balinese aesthetics, specifically the Patra Punggal motif. This touring fashion collection aims to introduce the diversity of traditional Balinese motifs to the larger community, particularly the Vespa community, which is spread throughout the archipelago and serves as a form of cultural preservation. The process of realizing this work goes through several stages: (1) the exploration stage, which includes observation and research, (2) the design stage, which involves creating several sketches and technical drawings, and (3) realization, which involves shaping the work and continuing to assess and evaluate the finished product. In the process of realizing this final project, the author used two types of materials: pull-up cowhide and sheepskin. The work created for this final project includes a leather jacket, a pair of gloves, a pair of boots, and a helmet.